Estimating of Fatty Acids, Tcopherols, Tocotrienols, Total Carotens, Study The Physiochemical Properties And Unsaponifiable Matters Extraction From Crude Red Palm Oil(1) (Baghdad Science Journal, 2025)
The percentage of fatty acids, quantity of tocopherols, tocotrienols, carotens and physiochemical characteristics of crude red palm oil have been evaluated, in addition to specific chemical detection of active compounds unsaponifiable matters. Results of Gas Liquid Chromatography showed:- The major fatty acids in red palm oil is palmitic (44.36%) then oleic (39.65%), linolenic (10.55%), stearic (3.56%), myristic (1.22%), arachdonic (0.24%) and palmotic (0.19%). Red palm oil contains ? – ?- ?- ? – Tocopherols with concentration 258 , 121 , 259, 109 m/kg oil , ? – ?- ?- ? – Tocotrienol with concentration 462.77 , 571.03, 619.18, 509.07 m/kg oil respectively. Total tocopherols & tocotrienols 2909.05 m/kg oil and 893.63 m/kg oil carotens. Results of physiochemical characteristics revealed that crude red palm oil contains 0.80 ± 0.13% moisture , 58.81 ± 0.24 iodin nomber, 210 ± 1.35 saponifid number, 0.417 pv, 0.7% unsaponifiable matters, 1.4684 refraction index. Specific chemical detection indicated that unsaponifiable matters contains phenols, flavonoids and sterols.